Exploration of The Whole Language Approach in Comprehensive Literacy Learning in SD/MI (A Systematic Literature Review) - Firna Nahwa Firdausi; Mohamad Zubad Nurul Yaqin; Bintoro Widodo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to explored the implementation of the whole language approach in comprehensive literacy learning in elementary school through the Systematic Literature Review (SLR) study. A total of 15 articles published in the 2021-2025 range were systematically analyzed using a selection protocol based on inclusion and exclusion criteria. The results of the study show that the whole language approach makes a positive contribution to the four literacy skills simultaneously, including reading, writing, speaking, and listening, through key components such as shared reading, guided writing, group discussions, storytelling, and daily journal writing. This approach has also proven to be relevant to strengthening 21st century competencies that include critical thinking, communication, collaboration, and creativity, as well as being in line with the principles of differentiated learning and strengthening the Pancasila Student Profile in the Independent Curriculum. Further research is recommended to explore the integration of digital and multimodal literacy within the framework of whole language to respond to the demands of the contemporary education ecosystem.